Magnetoelectric reduction of chromium(VI) to chromium(III). (March 2022) - Mushtaq, Fajer; Chen, Xiang-zhong; Veciana, Andrea; Hoop, Marcus; Nelson, Bradley J.; Pané, Salvador
Highlights: Magnetic fields directly reduce toxic heavy metals through magnetoelectric effect. 86% of toxic Cr (VI) can be reduced through this way. The presence of methylene blue accelerates the reduction of Cr (VI) to Cr (III). Concomitant metal reduction and organics degradation goes synergistically. Abstract: Toxic heavy-metal pollution represents one of the most pressing environmental challenges that humankind faces today. The conventional approaches for removing highly toxic and carcinogenic heavy metals are currently unsuitable for practical applications. The reduction of harmful heavy metals, such as hexavalent chromium (Cr(VI)) into less harmful trivalent chromium Cr(III), has been gaining considerable interest. In response to this, UV light based photocatalysts have been comprehensively investigated for the reduction of various problematic heavy metals. However, for practical applications, using light as a solution can be highly inefficient owing to poor light absorption in murky or colored heavy metal contaminated water. Here, we demonstrate that wireless magnetic fields can induce the reduction of toxic heavy metals. Core-shell magnetoelectric CoFe2 O4 @BiFeO3 nano-octahedral particles were fabricated and used for the catalytic reduction of Cr(VI) via the magnetoelectric effect. We have conducted trapping experiments to propose a mechanism behind the magnetoelectric-effect catalytic reduction. We have achieved reduction of 86% of toxic Cr(VI) using a scavenger for singlet oxygen. In addition, we show the concomitant reduction of Cr(VI) and degradation of an organic pollutant, methylene blue, in a synergistic manner, where the presence of methylene blue accelerates the reduction of Cr(VI) to Cr(III). Graphical abstract: Image, graphical abstract